Etiology, Management of Catheter-related Bladder Discomfort with Pharmacological Agents and Non-pharmacological Means - Mallik, Ashraf Uddin; Rahman, Md Mostafizur; Mazumdar, Rajib Kumar; Karmaker, Uttam; Rahman, Marufur; Samrat, Yeasir Arafat; Islam, Sanjida; Hossain, Forhad; Anni, Shanjida Khatun; Khatun, Sayma (KYAMC Journal, 2025)
Self-retaining balloon catheters are essential for effective urine drainage following urological and other major surgeries. However, their use can sometimes lead to catheter-related bladder discomfort (CRBD), a condition that causes significant distress, reduces quality of life, and requires prompt management. A systematic review was conducted using Medline, PubMed, Google, and CINAHL to identify relevant articles aligned with the study's objectives. A total of 13 articles were included in the review, with some from CINAHL specifically focusing on non-pharmaceutical approaches for managing CRBD symptoms. In addition to pharmaceutical treatments, several non-pharmaceutical interventions, easily implemented by nurses, were found effective. These include reducing the catheter balloon size, securely fixing the catheter, properly positioning the urine bag, using a catheter valve, addressing constipation, encouraging increased fluid intake, and recommending a diet rich in fluids and fiber. These measures were demonstrated to alleviate CRBD symptoms significantly. KYAMC Journal Vol. 16, No. 01, April 2025: 41-47